2019
DOI: 10.1101/647529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nuclear lamin B is crucial to the nuclear envelope integrity and extracellular trap release in neutrophils

Abstract: It's not clear how nuclear envelope (NE) is ruptured for chromatin externalization duringNETosis. The membrane rupture during neutrophil NET release was described as a membrane lysis process, this notion, however, has been questioned. Here, we found that lamin B, the structural NE component, was involved in NETosis. Unexpectedly, lamin B was not fragmented by destructive proteolysis, but rather disassembled into its intact full-length molecule, in NETotic cells with ruptured NE. In the mechanistic study, our e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…The formation of meshwork discontinuities could be the result of lamin posttranslational modifications. As such, lamin A/C (Amulic et al 2017) and PKCα-mediated lamin B1 (Li et al 2019) phosphorylation was reported in PMA-induced NETosis. Indeed, mutation of the PKC phosphorylation sites of lamin B1 impairs extracellular trap release in RAW264.7 macrophages (Li et al 2019).…”
Section: Lamin Dynamics During Netosismentioning
confidence: 81%
See 3 more Smart Citations
“…The formation of meshwork discontinuities could be the result of lamin posttranslational modifications. As such, lamin A/C (Amulic et al 2017) and PKCα-mediated lamin B1 (Li et al 2019) phosphorylation was reported in PMA-induced NETosis. Indeed, mutation of the PKC phosphorylation sites of lamin B1 impairs extracellular trap release in RAW264.7 macrophages (Li et al 2019).…”
Section: Lamin Dynamics During Netosismentioning
confidence: 81%
“…As such, lamin A/C (Amulic et al 2017) and PKCα-mediated lamin B1 (Li et al 2019) phosphorylation was reported in PMA-induced NETosis. Indeed, mutation of the PKC phosphorylation sites of lamin B1 impairs extracellular trap release in RAW264.7 macrophages (Li et al 2019). Additionally, lamin B1 degradation has been observed during ionomycin-induced NETosis (Gößwein et al 2019), and PAD4 deficiency has been shown to delay the formation of lamin discontinuities and to diminish lamin B1 degradation in ionomycin-stimulated neutrophils (Gößwein et al 2019, Thiam et al 2020.…”
Section: Lamin Dynamics During Netosismentioning
confidence: 81%
See 2 more Smart Citations